EXPERIMENTAL RESEARCHES OF JUMP-SHAPED CHANGES OF CURRENT AND VOLTAGE IN TRANSIENT SWITCHING CIRCUITS OF AC GENERATION - Tatenov, A.M.; Bugubaev, B.S.; Shilipko, V.V.; Akynov, M.N.; Baikadamova, L.S. (Academic Scientific Journal of Computer Science, 2020)
The article considers the transient process in switching electrical circuits, which are available in electric current generators in the form of a surge of supercurrents and voltage when removing, from isolated plates, brushes and which are lost in unused form. These bursts in collected form account for about-30-35% of the energy generated by the generator. The work is devoted to analysis of the available theoretical works on transients and experimental study of current surges and voltage in switching circuits, similar in electric motors and elk-regenerators. The results are given of the experimental study in the switching circuits of the electric generator in the work.